Photographing pattern & design in nature a close-up guide - Wilson, Arnold (A & C Black Publishers, 2010)
"This book contains many amazing images of patterns in nature as well as the information to help guide you towards making your own. Aimed at people who have used a camera before, but are looking to expand their knowledge, or for those who just want to have a go at close-up photography, it covers everything from choice of camera and use of lenses, to composition and the consideration of light and exposure. The author also looks at types of pattern, symmetry and texture found in a nature which can be exploited to capture fantastic photos. The book explains how to set up your photos in situ, exploring the best methods for capturing the shot, including the use of lights and tripod if needed. It also shows you how to bring the object inside and set up shoot indoors if necessary, in order to create a perfect photo set-up if the weather and conditions are not suitable. All in all, a compete guide to getting started in close-up photography, complete with some amazing photos of patterns found in everything from animals, flowers and leaves to insects and minerals." -- Provided by publisher